The Development of Student Worksheets (LKS) With Ethnomatematic Approach to Triangle Flat Build Material - Siti Fatmawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2020)
The purpose of this study is to describe the process and results of the development of Student Worksheets (LKS) with the ethnomatematics approach of triangular flat figure material. This type of research is development. This research was conducted on seventh grade students at MTs Al-Azhar Kaliwates Jember. The data collection methods used are documentation, observation, interviews and tests. The development model used adopted the 4D model developed by Tiagrajan through the stages of defining, designing, developing and distributing. Based on the research activities that have been carried out the results obtained are Student Worksheets (LKS) with ethnomatematics approach to the triangular flat figure material which is valid and suitable for use for junior high school students and equivalent Keywords: LKS, etomatematics